Mga piling awit at korido - Eugenio, Damiana L. (Diliman, Quezon City University of the Philippines Press, 1995)
Selected songs and religious poems sung in the church in the Philippines.
Includes bibliographical references.
In Tagalog.
Keywords: Hymns, Tagalog -- Texts